Preparation of Textured Surfaces on Aluminum-Alloy Substrates - Kadlečková, Markéta; Minařík, Antonín; Smolka, Petr; Mráček, Aleš; Wrzecionko, Erik; Novák, Libor; Musilová, Lenka; Gajdošík, Radek (Materials (Basel, Switzerland), 2018)
The ways of producing porous-like textured surfaces with chemical etching on aluminum-alloy substrates were studied. The most appropriate etchants, their combination, temperature, and etching time period were explored. The influence of a specifically textured surface on adhesive joints' strength or superhydrophobic properties was evaluated. The samples were examined with scanning electron microscopy, profilometry, atomic force microscopy, goniometry, and tensile testing. It was found that, with the multistep etching process, the substrate can be effectively modified and textured to the same morphology, regardless of the initial surface roughness. By selecting proper etchants and their sequence one can prepare new types of highly adhesive or even superhydrophobic surfaces.
Keywords: adhesive bonding; etching; superhydrophobic; duralumin; porous-like; surface texture; alloy; aluminum